Gamonalismo and Local Power Networks in the Northeast of Antioquia, (Colombia, 1930-1953) [Gamonalismo y Redes de Poder Local en el Nordeste Antioqueño, (Colombia, 1930-1953)] - Henao-Holguin, D (State University of Santa Catarina, 2019)
The phenomenon of gamonalismo in Ecuador is associated with a form of local political power, characterized as despotic, its livelihood is rural societies in which there is peasant subordination and dominance of large property. On the other hand, in Perú the phenomenon constitutes the traditional system of domination and is associated with the power exercised by landowners in the Sierra. In Colombia, the gamonal, despite being linked to the rural world, is not necessarily a large landowner. The gamonal acts as a link between the municipality and the department or even between the municipality and the central power. This article attempts to analyze the peculiarities of gamonalismo in the Northeast of Antioquia, a frontier area, where the colonization processes took place later than in the central zones of the department, therefore, it is a space of configuration of networks of power. In the primary sources researched (Gobierno/Municipios and Minas y Baldíos from the Historical Archive of Antioquia) the gamonal appears as an actor who restricts access to land to settlers, which implies that gamonalism in this subregion must be studied through the process of occupation of public lands and the conflicts derived from this dynamic. © 2019 State University of Santa Catarina. All rights reserved.